Modelling Event Systems for AmI Applications using an Aspect Middleware Platform - MEIER, RENE (My University, 2006)
The development of a communication service is one of the most difficult and important challenges when developing Ambient Intelligence (AmI) applications. Since AmI applications must be able to react to external events, event-based communication is a natural way to disseminate such events amongst all interested AmI components. A wide range of diverse event systems have been developed for addressing the problems on specific domains. Although AmI applications may benefit from the features of many of these event systems, middleware platforms for AmI applications typically support just one event system. Interconnecting different event systems in a multilateral inter-working federation will provide a homogeneous interface to access the specific services and features offered by each event system. This work presents an integration example of heterogeneous event systems in a homogeneous way through the use of an Aspect Oriented Middleware platform.
PUBLISHED
Keywords: Computer science; AO Middleware; Federated Event Systems